Rural Settlement: A Case of Barauli Village - AR. Sudarshana Arya (International Journal of Rural and Regional Development, 2023)
We see that there is a considerable change in their style when come with the same in urban areas. Life and living of rural people is viewed in terms of demography, employment and asset structure, agriculture and allied activities, rural poverty and livelihood, social and cultural issues, institutions, government schemes/programs, village-level amenities and linkages, energy utilization patterns, recent changes and development in the villages and surrounding areas, issues related to water supply, sanitation, solid waste management, public transport, water source development and water conservation, education, recreational facilities, health facilities, and information and communication technologies. The main objectives of rural study are to understand the location, spatial and economic linkages, the social and physical infrastructure, and the availability and usage of local resources of the villages. Furthermore, the study will investigate the present problems and future possibilities in the village and propose strategies to improve the condition and development of the village. The main purpose of the study is to prepare a comprehensive, realistic, and practical blueprint for the development of the village.
Keywords: Panchayati Raj; Rural society; Village Development Plan; community participation; infrastructure; landuse